Bio-Invigoration of DETAP-1 Soybean (Glycine max) Seeds Through PGPR Application - Pradana, Onny Chrisna P.; Noviana, Devi; Gut Tianigut; Hakim, Nurman A.; Dewi, Ratna (ABEC Indonesia, 2024)
Soybeans are a source of plant-based protein and a staple food ingredient, especially in Indonesia. Whenstored for extended periods, soybean seeds may experience quality deterioration, which can impact their productivity. Aneffort to improve the quality of deteriorated soybean seeds is through bio-invigoration treatment. The goal of bioinvigoration is to enhance seed metabolism through imbibition. One method that can be used as bio-invigorationtreatment is the application of plant growth-promoting rhizobium (PGPR). This research was conducted from May toJuly 2024 at the Seed Analysis Laboratory, Politeknik Negeri Lampung. The research was arranged in a CompletelyRandomized Design (CRD) with two factors, namely concentration (K) and soaking duration (L). For the concentrationfactor, there were four levels: 0% (K0), 6% (K1), 12% (K2), and 24% (K3), and the soaking duration factor consisted oftwo levels: 3 hours (L1) and 6 hours (L2). The factors were combined and repeated four (4) times, resulting in 32experimental units. Data were analyzed using variance analysis at 5% and 1% significance levels, and if significantdifferences were observed, further testing was conducted using the Least Significant Difference (LSD) test at the 5%level. The results showed that PGPR can improve the viability and vigor of Detap-1 soybean seeds that have experienceddeterioration. Treatment with 12% PGPR with a 6-hour soaking duration can increase the seed's germination byapproximately 11.33%, from the initial germination rate of 68% to 80%.